Role of exosomes in hepatocellular carcinoma and the regulation of traditional Chinese medicine - Yao, Man; Liang, Shufang; Cheng, Binbin (Frontiers in Pharmacology, 2023)
Hepatocellular carcinoma (HCC) usually occurs on the basis of chronic liver inflammatory diseases and cirrhosis. The liver microenvironment plays a vital role in the tumor initiation and progression. Exosomes, which are nanometer-sized membrane vesicles are secreted by a number of cell types. Exosomes carry multiple proteins, DNAs and various forms of RNA, and are mediators of cell-cell communication and regulate the tumor microenvironment. In the recent decade, many studies have demonstrated that exosomes are involved in the communication between HCC cells and the stromal cells, including endothelial cells, macrophages, hepatic stellate cells and the immune cells, and serve as a regulator in the tumor proliferation and metastasis, immune evasion and immunotherapy. In addition, exosomes can also be used for the diagnosis and treatment HCC. They can potentially serve as specific biomarkers for early diagnosis and drug delivery vehicles of HCC. Chinese herbal medicine, which is widely used in the prevention and treatment of HCC in China, may regulate the release of exosomes and exosomes-mediated intercellular communication. In this review, we summarized the latest progresses on the role of the exosomes in the initiation, progression and treatment of HCC and the potential value of Traditional Chinese medicine in exosomes-mediated biological behaviors of HCC.